Assessing potential health effect of lead and mercury and the impact of illegal mining activities in the Bonsa river, Tarkwa Nsuaem, Ghana - Abena Obiri-Yeboah, PhD; Emmanuel Kwesi Nyantakyi; Abdul Rahim Mohammed, BSc; Saeed Ibn Idris Kofi Yeboah, MSc; Martin Kyereh Domfeh, PhD; Ebenezer Abokyi, BSc (Scientific African, 2021)
Access to quality water remains critical for protecting communities against waterborne diseases worldwide. Potable and quality water penetration to most rural communities is minimal such that over 2.2 billion people worldwide are negatively affected. Activities such as illegal mining, domestic use of water in river bodies, discharge of untreated household and industrial waste into water bodies, and agricultural pollution among others result in pollution of water bodies thus impacting water quality. This study sought to ascertain and measure the actual environmental impact of illegal mining activities in the Bonsa river in the Tarkwa Nsuaem Municipal Assembly, Ghana. The river was partitioned into upstream, midstream, and downstream locations, and water samples were collected and subjected to physicochemical and heavy metal pollution analysis. The physicochemical characteristics in the Bonsa river revealed mean turbidity values of 155.75 NTU downstream, 135.0 NTU midstream, and 207.0 NTU upstream which exceeds the required international benchmark of the World Health Organization (WHO) for potable water. The heavy metal analysis of lead and mercury also showed values considerably higher than those permissible by the Ghana Environmental Protection Agency (EPA) and the WHO indicating significant contamination levels. The study concludes that based on the physicochemical and heavy metal analysis, the Bonsa river is not safe for consumption at all locations and recommends water purification measures before use. The authors recommend the need for preventing related socioeconomic and public health implications through public education initiating plans towards the containment of water pollution.